(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Genetic variability among the genotypes of any species could be utilized for its improvement. PCR-based Random Amplified Polymorphic DNA (RAPD) technique was used to determine the genetic diversity and relationship among 10 cucumber varieties and genotypes. Five decamer primers were used to amplify genomic DNA and the primers yielded a total of 54 bands of which 36 bands were polymorphic and 18 bands were monomorphic. The UPGMA dendrogram based on Neis (1972) genetic distance indicated segregation of 10 cucumber varieties and genotypes into two main clusters. Variety Joti alone grouped in cluster 1 while variety Green Master, Shahi-50, Shikha, Shila, Shital, Naogaon-5, Shohag-50, Giant Long and genotype CS-043 grouped in cluster 2. Variety Shila was very close to variety Shital with the least genetic distance (0.1712). The highest genetic distance (0.5352) was found between Joti and Naogaon-5. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17081 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):51-63, 2011